Biomechanical mechanisms of jumping performance in youth elite female soccer players - Jeras, N. M. J.; Bovend`Eerdt, T. J. H.; McCrum, C. (Journal of Sports Sciences, 2020)
We aimed to determine key biomechanical parameters explaining age-related jumping performance differences in youth elite female soccer players. Multiple biomechanical parameters from countermovement (CMJ) squat (SJ) and drop (DJ) jump testing of elite female soccer players (n = 60) within the same national training centre were analysed across ages 9-11y, 12-14y and 15-19y. Effects of age group and jump type on jump height were found, with the older jumping higher than the younger groups in all jumps (P < 0.05). For DJ, higher reactive strength index was found for older, compared to each younger group (P < 0.001). For CMJ and SJ, peak power was the most decisive characteristic, with significant differences between each group for absolute peak power (P < 0.0001) and body-weight-normalised peak power in CMJ (57 ± 7W/kg, 50 ± 7W/kg, 44.7 ± 5.5W/kg; P < 0.05) and between the older and each younger group in SJ (56.7 ± 7.1W/kg, 48.9 ± 7.1W/kg, 44.6 ± 6W/kg; P < 0.01). Age-related differences in jumping performance in youth elite female soccer players appear to be due to power production during standing jumps and by the ability to jump with shorter ground contact times during reactive jumps.